Carbon Literacy in Higher Education: A Systematic Review of CO₂ Emission Education and Its Impact on Student Behavioral Change - Iwan Maryawan; Herpratiwi Herpratiwi; Sowiyah Sowiyah; Melya Riniarti; Riswanti Rini; Rini Nurindarwati; Lia Nurbanillah Fujianti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Carbon literacy education has emerged as a key strategy for addressing climate change by enhancing environmental awareness and promoting pro-environmental behavior among university students. This study presents a systematic literature review examining how CO₂ emission education is conceptualized, implemented, and evaluated within higher education institutions and its influence on student behavioral change. This review synthesizes peer-reviewed studies published between 2015 and 2026, focusing on conceptual frameworks, pedagogical approaches, and behavioral outcomes. The findings indicate that carbon literacy education improves climate knowledge, strengthens environmental attitudes, and increases students’ intentions to adopt sustainable practices in the future. Pedagogical strategies, such as experiential learning, project-based learning, life cycle assessment, and campus-based sustainability initiatives, play a critical role in translating knowledge into actionable competencies. However, a persistent awareness–action gap remains, wherein increased knowledge does not consistently lead to sustained behavioral change. The effectiveness of educational interventions is strongly influenced by psychological engagement, social learning environments and institutional support. Overall, this study emphasizes the need for integrated and interdisciplinary approaches that combine cognitive, experiential, and institutional dimensions. Embedding carbon literacy across curricula and campus practices can enable higher-education institutions to foster meaningful behavioral change and contribute to climate-mitigation efforts.